1994
DOI: 10.1002/ajmg.1320540311
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of the dopamine D2receptor gene in Tourette's syndrome using the haplotype relative risk method

Abstract: Comings et al. [1991: JAMA 266: 1793-1800] have recently reported a highly significant association between Tourette's syndrome (TS) and a restriction fragment length polymorphism (RFLP) of the dopamine D2 receptor gene (DRD2) locus. The A1 allele of the DRD2 Taq I RFLP was present in 45% of the Tourette patients compared with 25% of controls. We tried to replicate this finding by using the haplotype relative risk (HRR) method for association analysis. This method overcomes a major problem of conventional case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…genotype has also been analyzed in a casecontrol genetic association study of Tourette's syndrome, which showed a significantly greater presence in patients (44.9 vs. 24.5%) (Comings et al 1991). Nevertheless, other reports have not replicated this finding (Nothen et al 1994;Gelernter et al 1994). …”
Section: Childhood Disordersmentioning
confidence: 92%
“…genotype has also been analyzed in a casecontrol genetic association study of Tourette's syndrome, which showed a significantly greater presence in patients (44.9 vs. 24.5%) (Comings et al 1991). Nevertheless, other reports have not replicated this finding (Nothen et al 1994;Gelernter et al 1994). …”
Section: Childhood Disordersmentioning
confidence: 92%
“…Thus, a model has been proposed in which frequent prefrontal activation during tic suppression may produce compensatory prefrontal cortex hypertrophy that aids in tic suppression [624,625], although it is not presently clear how such basal ganglia and prefrontal characteristics effects reward processing in TS. Variants in the DA receptor gene DRD 2 have also been associated with genetic risk for TS [626-628], but this finding is not consistent [629-633]. …”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, no association between the A1 allele and severity was observed [35]. Finally, using a family-based association strategy [48], did not find any evidence for a association between DRD2 and TS.…”
Section: Candidate Genesmentioning
confidence: 96%